SEJARAH PERKEMBANGAN MUHAMMADIYAH DI KOTA PONTIANAK DARI TAHUN 1990-2000 - Zahro, Hanifatuz; Noor, Agus Sastrawan; Firmansyah, Andang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research entitled â€œThe History of the development of Muhammadiyah in Pontianak from 1990-2000â€. The formulation of the problem in this study were: (1)how the background of the establishment of the Muhammadiyah organization in Pontianak, (2) how was the historical development of the Muhammadiyah organization in Pontianak from 1991-2000, (3) how was the role of Muhammadiyah leaders in Pontianak. The research method used in this study was the historicalmethod (historical methodology). The procedures that used in historical method that consist of topic selection, heuristics, verification, interpretation and historiography. From this study it was concluded that the establishment of Muhammadiyah in Pontianak City was marked by a visit sent by the PP Muhammadiyah Assembly Tabligh Yogyakarta namely UstadzChatibSyatibi at the end of 1932.The background of the founding of Muhammadiyah in Pontianak is to improve the teachings that are already unreasonable, meaning the teachings that do not enter alak are like superstition too trusting dukuns or inanimate objects. Muhammadiyah also wants to correct the irregularities that have occurred and advance social education in the city of Pontianak.Â Keywords: History, Development, Muhammadiyah, Pontianak